Strengthening of Steel Columns under Load: Torsional-Flexural Buckling - Martin Vild; Miroslav Bajer (Advances in Materials Science and Engineering)
The paper presents experimental and numerical research into the strengthening of steel columns under load using welded plates. So far, the experimental research in this field has been limited mostly to flexural buckling of columns and the preload had low effect on the column load resistance. This paper focuses on the local buckling and torsional-flexural buckling of columns. Three sets of three columns each were tested. Two sets corresponding to the base section (D) and strengthened section (E) were tested without preloading and were used for comparison. Columns from set (F) were first preloaded to the load corresponding to the half of the load resistance of the base section (D). Then the columns were strengthened and after they cooled, they were loaded to failure. The columns strengthened under load (F) had similar average resistance as the columns welded without preloading (E), meaning the preload affects even members susceptible to local buckling and torsional-flexural buckling only slightly. This is the same behaviour as of the tested columns from previous research into flexural buckling. The study includes results gained from finite element models of the problem created in ANSYS software. The results obtained from the experiments and numerical simulations were compared.